Isolation, serotype diversity and antibiogram of Salmonella enterica isolated from different species of poultry in India - Irfan Ahmad Mir (Asian Pacific Journal of Tropical Biomedicine, 2015)
Objective: To study the occurrence and serotype diversity of Salmonella isolates in different species of poultry (chicken, emu and duck) and determine their resistance pattern against various antibiotics of different classes. Methods: About 507 samples comprising 202 caecal contents and 305 fecal samples from chicken, emu and duck were processed for isolation of Salmonella enterica. Salmonellae were isolated and detected by standard protocol of ISO 6579 Amendment 1: Annex D. Genetic confirmation was also made by using 16S rRNA genus specific PCR. Serotype specific PCR was also done to detect the most common serovars viz. Salmonella Enteritidis, Salmonella Typhimurium and Salmonella Gallinarum. All obtained isolates were subjected to a set of 25 antibiotics to study their antibiogram by using Baeur–Kirby disk diffusion method. Results: Out of 507 samples processed, 32 isolates of Salmonella enterica (18 from caecal contents and 14 from faecal samples) were obtained, of which 24 belonged to 6 different serovars, 6 were untypeable and 2 were rough strains. Salmonella Enteritidis was the most predominant serotype (9), followed by Salmonella Typhimurium (5), Salmonella Virchow (4), Salmonella Gallinarum (3), Salmonella Reading (2) and Salmonella Altona (1). Antibiotic resistance pattern was maximum (100%) to oxacillin, penicillin and clindamycin, followed by ampicillin (68.75%), tetracycline (65.62%), nalidixic acid (56.25%) and colistin (46.87%). High sensitivity of isolates was recorded for chloramphenicol (96.87%) followed by meropenem (84.37%). Conclusions: Occurrence of high proportion of serovars in our study which can cause serious gastroenteritis in humans is a matter of concern. Salmonella Altona has been detected for the first time in India from poultry. This serotype is known to cause serious outbreaks of gastroenteritis in humans. Multidrug resistant isolates were recovered at high percentage which can be attributed to non-judicious use of antibiotics both in prophylaxis and treatment regimen. This observation draws serious attention as poultry serves as an important source of transmission of these multidrug resistant Salmonella serovars to humans.